Adventitious roots of wheat seedlings that emerge in oxygen-deficient conditions have increased root diameters with highly developed lysigenous aerenchyma - Yamauchi, Takaki (Taylor & Francis, 2014)
Exposing roots of plants to hypoxic conditions is known to greatly improve their anoxic stress tolerance. We previously showed that pre-treatment of wheat seedlings with an ethylene precursor, 1-aminocyclopropanecarboxylic acid (ACC), enhanced their tolerance of oxygen-deficient conditions. Although ACC-pretreated seminal roots of wheat seedlings grown under oxygen-deficient conditions avoided root tip death, they elongated very little. In the present study, we assessed the effects of ethylene on the responses of adventitious roots of wheat seedlings to oxygen-deficient conditions. Lysigenous aerenchyma formation in the adventitious roots of wheat seedlings pretreated with ACC appeared to reduce tip death under oxygen-deficient conditions, but the adventitious roots, like the seminal roots, hardly elongated. We also found that adventitious roots that emerge in oxygen-deficient conditions continued to elongate even under such conditions. The adventitious roots emerged in oxygen-deficient conditions were found to have thicker root diameters than those emerged in aerated conditions. These results suggest that the adventitious roots with thicker root diameters can better cope with oxygen-deficient conditions. Measurements of the area of the lysigenous aerenchyma confirmed that the increased root diameters have a greater amount of air space generated by lysigenous aerenchyma formation.